A sixteen-week three-armed, randomized, controlled trial investigating clinical and biochemical effects of targeted alterations in dietary linoleic acid and n-3 EPA+DHA in adults with episodic migraine: Study protocol. (January 2018) - Mann, John Douglas; Faurot, Keturah R.; MacIntosh, Beth; Palsson, Olafur S.; Suchindran, Chirayath M.; Gaylord, Susan Ann; Lynch, Chanee; Johnston, Angela; Maiden, Kristen; Barrow, David A.; Hibbeln, Joseph R.; Ramsden, Christopher E.
Abstract: Migraine is a prevalent neurological disorder, affecting over 16% of adult women and 7% of adult men in the U.S., causing significant pain, disability, and medical expense, with incomplete benefits from conventional medical management. Migraine, as a chronic pain syndrome, provides a practical model for investigating the impact of dietary modifications in omega-3 (n-3) and omega-6 (n-6) fatty acids. This paper reports the protocol of a trial to assess whether targeted dietary modifications designed to increase n-3 eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), with or without concurrent reduction in n-6 linoleic acid (LA), will alter nociceptive lipid mediators and mediate decreases in frequency and severity of migraine. This prospective, randomized, controlled trial in 153 male and female adult subjects, ages 18–99, with diagnosed and actively managed episodic migraine tests the efficacy, safety, and biochemical effects of targeted, controlled alterations in dietary omega-3 and omega-6 fatty acids. Participants are masked to diet hypotheses and all assessors are masked to treatment assignment. Following a four-week baseline period, participants with migraine headache frequency of 5–20 per month are randomized to one of three intensive dietary regimens for 16 additional weeks followed by a less intensive observation period. Dietary intervention arms include: 1) increased n-3 EPA+DHA with low n-6 linoleic acid (H3 L6); 2) increased n-3 EPA+DHA with usual US dietary intake of n-6 linoleic acid (H3 H6); and 3) usual US dietary content of n-3 and n-6 fatty acids (L3 H6). During the actual intervention, subjects receive content-specific study oils and foods sufficient for two meals and two snacks per day, as well as dietary counseling. Biochemical and clinical outcome measures are performed at intervals throughout this period. This randomized controlled trial is designed to determine whether targeted alterations in dietary n-3 and n-6 fatty acids can alter nociceptive lipid mediators in a manner that decreases headache pain and enhances quality of life and function in adults with frequent migraines. Trial registration: NCT02012790 Highlights: Lipid mediators derived from n-3 and n-6 fatty acids are proposed to regulate pain. Targeted changes in fatty acids reduced headaches in a prior, small randomized trial. The protocol for an ongoing larger, more tightly controlled trial is presented.